Post-functionalization of polyvinylcarbazoles: An open route towards hole transporting materials for perovskite solar cells. (15th November 2019) - Geffroy, Camille; Grana, Eftychia; Mumtaz, Muhammad; Cojocaru, Ludmila; Cloutet, Eric; Olivier, Céline; Uchida, Satoshi; Toupance, Thierry; Segawa, Hiroshi; Hadziioannou, Georges
Graphical abstract: Highlights: Original synthesis of poly(9-vinylcarbazole)-based hole transporting materials (HTM). Undoped PVK-[N(PhOCH3 )2 ]2 with hole mobility one order of magnitude higher than pristine spiro-OMeTAD. Doped PVK-[N(PhOCH3 )2 ]2 with hole mobility one order of magnitude higher than doped spiro-OMeTAD. As HTM in n-i-p mesoscopic PSCs, PVK-[N(PhOCH3 )2 ]2 yielded PCEs up to 16.7%. Extended PSC life-time using PVK-[N(PhOCH3 )2 ]2 as HTM without encapsulation. Abstract: We report on the potential of tuning poly(9-vinylcarbazole) (PVK) properties through functionalization for an application as hole transport material (HTM) for perovskite solar cells (PSCs). The synthesized PVK-based polymers were substituted with moieties of interest to improve the solubility, the charge transport properties, or to tune energy levels. Bis(4-methoxyphenyl)amine moieties were found to improve the hole mobility and to increase the HOMO level of the PVK. Therefore, PSCs employing PVK-[N(PhOCH3 )2 ]2 as HTM exhibited a best PCE of 16.7%. Compared to spiro-OMeTAD, first studies have shown that PVK-[N(PhOCH3 )2 ]2 could extend PSC lifetime.